2015
DOI: 10.1016/j.apcatb.2014.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Pd catalysts supported onto nanostructured carbon materials for CO2 valorization by electrochemical reduction

Abstract: Pd nanoparticles have been supported onto different novel carbon materials to be used in the electroreduction of CO 2 to high-added value products. Carbon nanocoils (CNCs), carbon nanofibers (CNFs) and ordered mesoporous carbon materials (OMCs) have been studied as support of the catalysts. In addition, Pd catalyst supported onto Vulcan XC-72R has been synthesized in order to establish a comparison with the commercial support. In this way, the influence of the carbon material on the physicochemical and electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(53 citation statements)
references
References 62 publications
6
47
0
Order By: Relevance
“…Indeed, Pérez‐Rodríguez et al. suggested that CO 2 reduction at Pd nanoparticles leads to the formation of a range of adsorbed intermediates such as HCOO ads , HCO ads and CH x species, which can be linked to the oxidation current observed in the positive‐going scan . However, these responses can be associated with H desorption processes that are shifted to more positive potentials because of surface‐adsorbed species formed previously during CO 2 reduction …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Indeed, Pérez‐Rodríguez et al. suggested that CO 2 reduction at Pd nanoparticles leads to the formation of a range of adsorbed intermediates such as HCOO ads , HCO ads and CH x species, which can be linked to the oxidation current observed in the positive‐going scan . However, these responses can be associated with H desorption processes that are shifted to more positive potentials because of surface‐adsorbed species formed previously during CO 2 reduction …”
Section: Resultssupporting
confidence: 93%
“…Therefore, all electrochemical signals and any products formed can be attributed directly to the reduction of dissolved CO 2 . In view of the pH sensitivity of the CO 2 reduction reaction, control experiments require the solution pH to be the same in the absence and presence of CO 2 , which is often overlooked . Accordingly, the pH of Ar‐saturated Na 2 SO 4 was adjusted to pH 4 using 0.5 m H 2 SO 4 to ensure that it was the same pH as the CO 2 ‐saturated electrolyte.…”
Section: Resultssupporting
confidence: 66%
“…One challenge for CO 2 reduction is to compete with facile hydrogen evolution reaction (HER) that lowers Faradaic efficiencies toward products from CO 2 reduction [2]. Both CO 2 reduction and HER are closely associated with the adsorbed hydrogen that not only is a key intermediate for HER [3,4], but also participates in the formation of intermediates derived from adsorbed CO 2 [5][6][7][8][9]. Therefore, the reaction pathway of the adsorbed hydrogen on active sites plays important roles in activity and selectivity toward CO 2 reduction.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] The property of metal nanoclusters is one of the major factors in determining catalytic performance. [6][7][8][9] However, the nature of support materials often has a substantial influence on the adsorption ability and catalytic activity of metal nanoclusters.…”
Section: Introductionmentioning
confidence: 99%